Auricularia Polytricha (Mushroom) Regulates Testicular DNA Expression and Oxidative Stress Markers of Streptozotocin-Induced Diabetic Male Wistar Rat - Agbor, Cyril Abang; Anyanwu, G. E (International Journal of Nutrition, 2020)
Local Nigerian men have been using AuriculariaPolytricha as a treatment for sexual dysfunction without supporting evidence from scientific experiments. This study was to investigate the effect of ethanolic extract of A. Polytricha on testicular DNA expression and some oxidative stress markers using STZ-Induced diabetic rats as a model. The experiment included six groups, Group A (Normal Control, treated with normal saline), Group B (treated with 65mg/kg.bw of STZ), Groups C, D, and E (treated with 250mg/kg.bw, 500mg/kg.bw, 1000mg/kg.bw AP after inducing diabetics), and Group F (treated with 40mg/kg.bw metformin after inducing diabetics). The experiment lasted for 35 days. After termination of the experiment, Fuelgen nuclear reaction was used for DNA demonstration to assess testicular DNA distribution while serum Superoxide Dimutase (SOD), Catalase and Melondialdehyde where evaluated using reagent based antioxidant enzyme assay. Results reveals that SOD and Melondialdehyde activities were remarkably (p<0.05) higher in diabetic control animals when compared with the normal control group. Values in Groups C, D and F that were administered with 250, 500mg/kg.bw A. polytricha and metformin respectively were also significantly (p<0.05) increased when compared with the normal control group. However, diabetic animals placed on 1000mg/kg.bw A. polytrichadid not show any statistical significance in comparison with normal control group but was remarkably (p<0.01) decreased when compared to the diabetic group that received low dose A. polytricha, an indication that the reversal is dose dependent. Catalase concentration in diabetic control animals was remarkably (p<0.05) higher when compared to the normal control but was not significantly (p<0.05) different in groups D (DM+500mg/kg.bw A. polytricha) and E (DM+1000mg/kg.bw A. polytricha) when compared with the normal control group. Diabetic control animals showed reduced magenta colour intensity of DNA and increased clustering and cross linking of DNA strands when compared with the normal control. However the degree of cross link in DNA strands was reduced in the diabetic animals placed on 1000mg/kg.bw A. polytrichawhen compared with the diabetic control group. Reversal in DNA damage and values of serum oxidative stress markers following administration of graded doses of A. polytricha could be attributed to essential phytochemical and therapeutic constituents in A. polytricha like polyphenol and flavonoid which can be found useful in prevention and treatment of diabetes induced testicular dysfunction. In summary, AP can contribute to a reversal in DNA damage and levels of serum oxidative stress markers in treating diabetes-induced testicular dysfunction.
Keywords: Auriculariapolytricha; Testicular DNA; Oxidative Stress Markers; Hyperglycaemia